2023
DOI: 10.1039/d2cp05272e
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic heterocyclic anion based ionic liquids and electrolytes

Abstract: Five new ionic materials comprising fluorine-free aromatic heterocyclic anions based on pyridine and pyrazine combined with a common n-tetrabutylphosphonium cation, (P4444)+, result in two room temperature ionic liquids (RTILs), one...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…This suggests efficient ion dissociation with increasing temperature, leading to homogeneity, which agrees well with the ionic conductivity and ion diffusivity data, and also to our previous study. [18] The chemical environment in the electrolytes is strongly affected by increased temperature, but the electrolytes are influenced differently. The chemical shift of Li + in [(MMBIm)(MEEA)] 0.7 [(Li)(MEEA)] 0.3 moves towards lower ppms, while for [(MBPyrr)(MEEA)] 0.7 [(Li)(MEEA)] 0.3 it shifts towards higher ppms (Figure 9b).…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…This suggests efficient ion dissociation with increasing temperature, leading to homogeneity, which agrees well with the ionic conductivity and ion diffusivity data, and also to our previous study. [18] The chemical environment in the electrolytes is strongly affected by increased temperature, but the electrolytes are influenced differently. The chemical shift of Li + in [(MMBIm)(MEEA)] 0.7 [(Li)(MEEA)] 0.3 moves towards lower ppms, while for [(MBPyrr)(MEEA)] 0.7 [(Li)(MEEA)] 0.3 it shifts towards higher ppms (Figure 9b).…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…For internal factors, the types of cation and anion can affect the conductivity of ILs. [55][56][57] The wide electrochemical window and superior electrochemical performance of ILs lead to their application in diagnostic medicine, such as using as an electrolyte and a modified electrode in the production and improvement of the performance of sensors.…”
Section: Physicochemical Properties Of Ilsmentioning
confidence: 99%
“…The anion also plays an important role in the overall physicochemical and electrochemical properties, including the mobility of the Li + ions – via ion‐ion and other interactions [25] . While many studies of IL‐based electrolytes have been reported during the last two decades, [26–28] most use commercially available ILs [29] and only few new anions have been reported [30–34] . Here we present a new class of fluorine‐free ILs and their corresponding electrolytes based on anions with aromatic centre and different oligoether chains.…”
Section: Introductionmentioning
confidence: 98%
“…[25] While many studies of IL-based electrolytes have been reported during the last two decades, [26][27][28] most use commercially available ILs [29] and only few new anions have been reported. [30][31][32][33][34] Here we present a new class of fluorine-free ILs and their corresponding electrolytes based on anions with aromatic centre and different oligoether chains. The use of a carboxylate group alongside an ether oxygen atoms containing chain, make these anions mimic the organic solvents commonly used in LIBs, such as glymes, [35][36][37] and carbonates, [38,39] but with the idea of the advantageous IL properties added in the design -and therefore systematic correlations between anions/ILs and key physicochemical properties are developed, with an emphasis on the ion transport and usefulness as battery electrolyte components.…”
Section: Introductionmentioning
confidence: 99%